Exploration of Hospital Management and Organization Strategies: A Literature Review of Health Services - Zainul Wasik; Didik Setiawan; Achmad Saiful Ulum (Journal of Managerial Sciences and Studies, 2024)
Background - Healthcare management strategy and organization encompasses the principles and practices used to operate healthcare facilities efficiently and effectively. It involves the planning, implementation, and coordination of various activities to ensure the delivery of high-quality patient care while optimising resource utilisation. The literature review in healthcare provides valuable insights into various aspects of hospital management strategy and organization. Objective - This article aims to find out the importance of management and organizational strategies in service businesses (hospitals) and related factors, so as to create improved human resource performance related to achieving effective and efficient organizational goals to face business competition and can be an organizational strategy in creating job satisfaction, can perform well and can create a competitive advantage for organizations in health services. Research Methode - The method used is the identification of previous articles with a total of 29 articles in the time span of 2000-2023. Search data for literature review was conducted in international journals to support the theory and take the topic of Management and Organizational articles, found 234,347 articles, scope Innovation, 2000-2023, Business, management and accounting, article, organization and management, English found 1,239 articles, Qualitative - 363 articles, Strategic - 134 articles, Performance - 95 articles, Effectiveness - 52 articles, Leadership, Health - 35 articles. Furthermore, articles that do not fit the topic will be ignored. Researchers only use data bases from Scopus and Web of Science because researchers only look for quality articles and the results are more accurate and very credible sources, because the results can be used as references and policies. Results - The importance of the role of management and organization in hospitals and can have a major impact on healthcare organizations. As explained in previous research that Management has a big role to improve hospital performance in an organization. The importance of management and organizational performance as they relate to each other. Human resources (HR) provide special attention in personal development and impact on performance in creating a health service. Conclusion - Management and organization are important in the hospital business because human resources are the driving force of the service business. Good management and organization can create professional and talented human resources results that can improve performance and will have an impact on organizational goals, and services to patients can run well which has an impact on the main objectives of the hospital. Management can be seen from several things including training and development, management practices, organizational climate, and other things that have a relationship in creating effective and efficient management so as to provide optimal results for the organization. Managerial Implications - The healthcare management needs to pay more attention to the evaluation of healthcare operational activities and feedback provided by patient families, the hospital management needs to increase the frequency of its discussions with employees to maintain excellent service quality for patient families, and the hospital management leaders need to set an example and encourage their employees to maintain a good organizational culture in order to maintain their service image.